2004
DOI: 10.1007/s11910-004-0044-2
|View full text |Cite
|
Sign up to set email alerts
|

Statins as potential therapeutic agents in multiple sclerosis

Abstract: 3-Hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase inhibitors (ie, statins) are oral cholesterol-lowering drugs. Statins are well tolerated and have an excellent safety record. These agents competitively inhibit HMG CoA reductase, which is the enzyme that catalyzes the conversion of HMG CoA to L-mevalonate. Although L-mevalonate is a key intermediate in cholesterol synthesis, several of its metabolites are involved in post-translational modification of specific proteins involved in cell proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Another transcript with elevated expression was Cd36, a multiligand scavenger receptor expressed by the cell of the monocyte/ macrophage lineage (including microglia) that plays important roles in cell attachment, motility, and proliferation as well as atherosclerosis, inflammation, thrombosis, TGF-␤ activation, neurite outgrowth, and angiogenesis (29). Statins, an effective cholesterollowering family of drugs, are highly effective in treating EAE, and clinical trials in MS patients are currently under way (30,31). Surprisingly, it has been recently shown that statins are potent activators of Cd36 transcription and translation in human monocytes (32).…”
Section: Discussionmentioning
confidence: 99%
“…Another transcript with elevated expression was Cd36, a multiligand scavenger receptor expressed by the cell of the monocyte/ macrophage lineage (including microglia) that plays important roles in cell attachment, motility, and proliferation as well as atherosclerosis, inflammation, thrombosis, TGF-␤ activation, neurite outgrowth, and angiogenesis (29). Statins, an effective cholesterollowering family of drugs, are highly effective in treating EAE, and clinical trials in MS patients are currently under way (30,31). Surprisingly, it has been recently shown that statins are potent activators of Cd36 transcription and translation in human monocytes (32).…”
Section: Discussionmentioning
confidence: 99%
“…Statins downregulate transporter 1, which may affect the so-called reverse cholesterol transport system [61], but could also alter peptide presentation by APCs. It is possible that some of the effects of statins in EAE and potentially in MS could be due to this activity [62,63].…”
Section: Major Histocompatibility Complex (Mhc)mentioning
confidence: 99%
“…Much of the current understanding of the treatment comes from the Optic Neuritis Treatment Trial (ONTT). 4 In recent years, small-scale clinical trials have indicated that statins or 3-hydroxy-3-methylglutaryl coenzyme A (HMGCoA) reductase inhibitors exert pleiotropic immunomodulatory effects, with potential therapeutic implications in MS. [5][6][7][8][9][10] The mechanism by which statins may play a role in autoimmunity involves the inhibition of HMGCoA reductase. Besides the biosynthesis of cholesterol, this enzyme regulates the biosynthesis of isoprenoids, which results in a decrease of autoimmune responses.…”
Section: Introductionmentioning
confidence: 99%